Understanding Underachievement: Mindset, Perfectionism, and Achievement Attitudes Among Gifted Students. (June 2019) - Mofield, Emily; Parker Peters, Megan
The current study compared differences between mindset beliefs about intelligence (fixed vs. growth), dimensions of perfectionism (Concern Over Mistakes, Doubt of Action, Personal Standards, Organization), and achievement attitudes among gifted underachievers ( n = 15) and gifted achievers ( n = 169) in Grades 6 to 8 and examined the relationship between mindset beliefs and dimensions of perfectionism. Gifted underachievers had higher fixed mindset beliefs about intelligence ( d = .79), lower scores on Organization ( d = −1.01), and lower Self-Regulation/Motivation ( d = −1.17) when compared with gifted achievers. These factors also were statistically significant in logistic regression models predicting achievement status. In addition, for the entire sample of gifted students ( N = 264), fixed mindset beliefs predicted both dimensions of Evaluative Concerns Perfectionism (Concern Over Mistakes, β = .35, p < .0001; Doubt of Action, β = .28, p < .0001), while growth mindset beliefs predicted both dimensions of Positive Strivings Perfectionism (Personal Standards, β = .35, p < .0001, and Organization, β = .21, p = .001). Our findings provide a clearer picture of the relationships among underachievement, perfectionism, implicit theories of intelligence, and achievement attitudes, providing guidance for affective interventions.